THE EFFECT OF AWARENESS, MORALITY, TAX CULTURE, AND DISTRIBUTIVE JUSTICE ON THE TAXPAYER COMPLIANCE - Ina Nurlela; Asep Kurniawan; Indah Umiyati (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
This study aims to determine the effect of awareness, morality, tax culture and distributive justice on the taxpayer compliance partially and simultaneously. The data used in this study are primary data by distributing questionnaires. The method used in sampling is a non probability sampling method with incidental sampling technique and the number of samples in this study amounted to 107 respondents consisting of perpetrator Small and Medium Enterprise (SMEs). The data is processed using the classical assumption test method, multiple linear regression analysis, t test, and F test. The results showed that partially (t test), the variable understanding of morality and tax culture had a positive effect on the taxpayer compliance of Small and Medium Enterprise (SMEs). While the variable awareness and distributive justice did not affect the taxpayer compliance of Small and Medium Enterprise (SMEs). Simultaneous results (F test) show that awareness, morality, tax culture and distributive justice on the taxpayer compliance.